Vers une micropolitique des formats - Guillaume Heuguet (Revue d'anthropologie des connaissances)
This article crosses perspectives from science studies, French information and communication sciences and cultural studies. We analyze the Content ID apparatus published by the company and video publishing site YouTube, which identifies the music tracks present in its videos to allow for them to be monetized. Such a study involves analyzing the construction of an innovation bridging the music and internet markets. Content ID is part of the lineage of strategic issues and techniques related to the music industry and the Web economy, which concern the arbitration between the circulation of cultural forms and their control as works and goods covered by copyright: in this context, Content ID is presented as the best compromise. The implementation of this compromise is based on the anchoring of the musical work in sound, its modeling through data, and the naturalization of this model. Beyond the technical equipment of market rules, Content ID works as a semi-automation of cultural and legal judgments of originality. It thus discreetly redefines the values of recorded music, and the way they are institutionalized.